Answer:
D. y = (x - 3)²
Step-by-step explanation:
The parabola formula in vertex form is:
y = a(x - h)² + k
where the vertex is located at (h, k). Replacing with vertex (3, 0) we get:
y = a(x - 3)² + 0
y = a(x - 3)²
In all possible options the leading coefficient <em>a</em> is equal to one. Therefore:
y = (x - 3)²
It took 11 hours to change!
Answer:
The product mass function is calculated taking different values of x=1,2,3,4.....
Answer:
Part A
to the 10th power will be positive and to the 11th power is negative. When the exponent is even it will be positive. When it is odd it will be negative
Part B
The one with the negative enclosed will be positive. The second one, the exponent is only effecting the number and not the sign. The outcome will always be negative.